Hubungan Pengetahuan Pria (PUS) dengan Minat Keikutsertaan sebagai Calon Akseptor Vasektomi di UPTD Puskesmas Cilodong 2025 - jihan amalia putri; Hesti Kusumaningrum; Christin Jayanti (Program Studi D III Kebidanan Akademi Kesehatan Sapta Bakti Bengkulu, 2026)
Male participation in family planning programs, particularly through vasectomy, remains relatively low. This condition is presumed to be associated with the level of knowledge among men of reproductive age couples regarding vasectomy, including understanding of procedures, benefits, and effects. This study aimed to determine the relationship between the level of knowledge and the interest of men of reproductive age couples in participating as prospective vasectomy acceptors at the Cilodong District Public Health Center in 2025. This study employed a quantitative method with a correlational design and a cross-sectional approach. A total of 92 respondents were selected using purposive sampling. Data were collected through questionnaires measuring knowledge and interest, and analyzed using univariate and bivariate analyses with the Chi-Square test at a significance level of α = 0.05. The results indicated that most respondents had a moderate level of knowledge and a moderate level of interest. Bivariate analysis revealed a statistically significant relationship between knowledge level and interest in participating as prospective vasectomy acceptors (p-value < 0.001). In conclusion, knowledge level is significantly associated with men’s interest in vasectomy participation. Strengthening education and reproductive health counseling for men is necessary to enhance male involvement in family planning programs.